Investigating resting-state functional connectivity of the human hand motor system: an offline TMS-fMRI study - Enrica Pierotti; Chiara Speranza; Luigi Cattaneo; Luca Turella (NeuroImage)
Skillful hand motor control engages complex interactions within a widespread brain network. Previous studies in non-human primates provided a precise picture of its connectivity profiles. Yet, whether the human hand motor network shows a similar connectivity fingerprints is still unclear. Our aim was to better characterize its functional connectivity profiles.We combined offline Transcranial Magnetic Stimulation (TMS) with resting-state functional magnetic resonance imaging (RS-fMRI) to map the changes in functional connectivity following the stimulation of a key node in this network, the human Anterior Intraparietal area (hAIP). Participants underwent two sessions of RS-fMRI before and after offline TMS, applied with a continuous theta-burst stimulation (cTBS) protocol.Univariate and multivariate analyses of RS-fMRI connectivity were performed. Univariate results showed that RS connectivity profiles within the hand motor network changed after cTBS to hAIP. Namely, we found increased functional connectivity between hAIP and SMA, and between SMA and M1. In multivariate analysis, we adopted a classifier to distinguish between RS-connectivity before and after cTBS. We showed significant decoding within a wide brain network comprising regions of the fronto-parietal motor pathways, of the ventral stream and within the cerebellum.Overall, our data provided novel insights on the connectivity patterns of the human hand motor network which compared favorably to the brain architecture described in monkeys, but with some species-specific features, advocating a similar crucial role of this network for hand action processing also in our species.